Material profile influences in bulk‐heterojunctions. Issue 19 (6th August 2014) - Roehling, John D.; Rochester, Christopher W.; Ro, Hyun Wook; Wang, Peng; Majewski, Jaroslaw; Batenburg, K. Joost; Arslan, Ilke; Delongchamp, Dean M.; Moulé, Adam J.
ABSTRACT The morphology in mixed bulk‐heterojunction films are compared using three different quantitative measurement techniques. We compare the vertical composition changes using high‐angle annular dark‐field scanning transmission electron microscopy with electron tomography and neutron and x‐ray reflectometry. The three measurement techniques yield qualitatively comparable vertical concentration measurements. The presence of a metal cathode during thermal annealing is observed to alter the fullerene concentration throughout the thickness of the film for all measurements. However, the absolute vertical concentration of fullerene is quantitatively different for the three measurements. The origin of the quantitative measurement differences is discussed. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 1291–1300